2010
DOI: 10.1007/s10490-009-9188-6
|View full text |Cite
|
Sign up to set email alerts
|

Behind M&As in China and the United States: Networks, learning, and institutions

Abstract: Mergers and acquisitions, Alliance network, Network and learning factors, China, United States,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 44 publications
(65 reference statements)
3
41
0
Order By: Relevance
“…As a family of theories, the institution-based view has now given birth to an institution-based view of corporate governance (Globerman, Peng, & Shapiro, 2011;Jiang & Peng, 2011;Lu, Au, Peng, & Xu, 2013;Peng & Jiang, 2010;Sauerwald & Peng, 2013;Van Essen, Huegens, Otten, & van Oosterhout, 2012;Young, Peng, Ahlstrom, Bruton, & Jiang, 2008), an institution-based view of corporate diversification (Kim et al, 2010;Lee, Peng, & Lee, 2008;Peng, Lee, & Wang, 2005), an institution-based view of mergers and acquisitions (Lin, Peng, Yang, & Sun, 2009;Yang, Sun, Lin, & Peng, 2011), and an institution-based view of knowledge management and intellectual property rights (Khoury & Peng, 2011;Lu et al, 2008;Mahlich, 2010;Peng, 2013). Clearly, the institution-based view has been significantly deepened and broadened recently.…”
Section: Resultsmentioning
confidence: 99%
“…As a family of theories, the institution-based view has now given birth to an institution-based view of corporate governance (Globerman, Peng, & Shapiro, 2011;Jiang & Peng, 2011;Lu, Au, Peng, & Xu, 2013;Peng & Jiang, 2010;Sauerwald & Peng, 2013;Van Essen, Huegens, Otten, & van Oosterhout, 2012;Young, Peng, Ahlstrom, Bruton, & Jiang, 2008), an institution-based view of corporate diversification (Kim et al, 2010;Lee, Peng, & Lee, 2008;Peng, Lee, & Wang, 2005), an institution-based view of mergers and acquisitions (Lin, Peng, Yang, & Sun, 2009;Yang, Sun, Lin, & Peng, 2011), and an institution-based view of knowledge management and intellectual property rights (Khoury & Peng, 2011;Lu et al, 2008;Mahlich, 2010;Peng, 2013). Clearly, the institution-based view has been significantly deepened and broadened recently.…”
Section: Resultsmentioning
confidence: 99%
“…A stream of recent work has increasingly recognized that firms often draw on behavioral learning to make acquisition decisions (Haleblian, Kim, & Rajagopalan, 2006;Hitt, Harrison, & Ireland, 2001;Levinthal & March, 1993;Vermeulen & Barkema, 2001;Zollo & Reuer, 2010). Another stream of research has suggested that firms are embedded in networks of relationships that can have a strong bearing on acquisitions (Haunschild, 1993;Lin, Peng, Yang, & Sun, 2009;Palmer, Barber, Zhou, & Soysal, 1995;Rangan, 2000;Yang, Sun, Lin, & Peng, 2011). In this article, we extend and bridge these two previously separated streams of research to explore some critical but often underexplored drivers for acquisitions.…”
mentioning
confidence: 85%
“…Rather than being atomistic players detached from their unique histories and broad contexts, firms are relational entities within alliance networks (Uzzi, 1996). Consequently, firms' decisions to acquire alliance partners cannot be separated from either their past experiences or their embeddedness in the alliance relationships (Lin et al, 2009;Yang et al, 2011).…”
Section: Alliance Learning Network Embeddedness and Acquisitionsmentioning
confidence: 99%
“…From a resource-based view, a hypothetical Chinese firm that is cross-listed on the NYSErelative to its non-cross-listed Chinese competitors-is in a better and more advantageous position to expand its geographic scope by undertaking M&As in the United States (Deng, 2009;Peng & Blevins, 2012;Yang et al, 2011). From an institution-based view, cross-listing reduces the liability of foreignness by enabling the use of the NYSE-traded shares to acquire targets in the United States (Bell et al, 2012).…”
Section: Cross-listing and The Geographic Scope Of The Firmmentioning
confidence: 99%